2022
DOI: 10.3390/w14030444
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Differences in Water Pollution and Liver Histopathology of Iberian Barbel (Luciobarbus bocagei) and Douro Nase (Pseudochondrostoma duriense) in an Agricultural Watershed

Abstract: Histopathology has been used as a very useful tool to provide information on the severity of tissue damage, injuries, and organ functionality. Thus, this work aimed to assess whether seasonal variations (summer and winter) in water quality had consequences on the liver histology of Iberian barbel (Luciobarbus bocagei) and Douro nase (Pseudochondrostoma duriense). The research was carried out in the Vilariça River, a tributary of the Sabor River in Portugal, which is used as spawning grounds by these endemic cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
3
8
0
1
Order By: Relevance
“…Consistently with this idea, we observed infiltration of lymphocytes in the liver parenchyma in the present study. These results coincide with the analyses reported on fish [63] and frogs [57] exposed to insecticides, and they may be due to atrazine's ability to induce an immune response. In addition, lymphocyte infiltration is related to inflammation, edema, fibrosis, and liver degeneration [63].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistently with this idea, we observed infiltration of lymphocytes in the liver parenchyma in the present study. These results coincide with the analyses reported on fish [63] and frogs [57] exposed to insecticides, and they may be due to atrazine's ability to induce an immune response. In addition, lymphocyte infiltration is related to inflammation, edema, fibrosis, and liver degeneration [63].…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, this damage can obstruct circulation and block blood flow [72]. In the present study, we observed congestion of the blood vessels, which corresponds to findings in other aquatic organisms [63]. Liver analysis determines that the congestion of blood vessels could also cause hepatocyte degeneration and necrosis [67,73].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Inside the body, NO 3 -N causes physiological and behavioral alterations (Torno et al, 2018;Yang et al, 2019;Yu et al, 2021). The liver is the detoxifying organ and its condition indicates environmental quality (Corredor-Santamaría et al, 2021;Tramunt et al, 2021;Santos et al, 2022). Toxic pollutants cause functional alterations of the gills and liver, such as gas exchange failure and metabolic damage.…”
Section: Introductionmentioning
confidence: 99%